2010
DOI: 10.1016/j.yfrne.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic effects of endocrine-disrupting chemicals on female reproduction: An ovarian perspective

Abstract: The link between in utero and neonatal exposure to environmental toxicants, such as endocrinedisrupting chemicals (EDCs) and adult female reproductive disorders is well established in both epidemiological and animal studies. Recent studies examining the epigenetic mechanisms involved in mediating the effects of EDCs on female reproduction are gathering momentum. In this review, we describe the developmental processes that are susceptible to EDC exposures in female reproductive system, with a special emphasis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 359 publications
(461 reference statements)
2
103
0
2
Order By: Relevance
“…20,25 However, it is also becoming apparent that histone modifications and ncRNAs, such as miRNAs, may also be involved. [25][26][27][28][29][30][31] We therefore analyzed the miRNA content of spermatozoa from five healthy smokers and five healthy non-smokers, identifying 130 known miRNAs common to all samples. A recent study has also detected miRNAs, together with other ncRNAs, such and other environmental chemical exposures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,25 However, it is also becoming apparent that histone modifications and ncRNAs, such as miRNAs, may also be involved. [25][26][27][28][29][30][31] We therefore analyzed the miRNA content of spermatozoa from five healthy smokers and five healthy non-smokers, identifying 130 known miRNAs common to all samples. A recent study has also detected miRNAs, together with other ncRNAs, such and other environmental chemical exposures.…”
Section: Discussionmentioning
confidence: 99%
“…environmental chemicals and factors, but may also be involved in the transmission of any resulting phenotypes to future generations. [25][26][27][28] There has been particular interest in an RNA-mediated form of non-Mendelian inheritance called paramutation. First identified in plants over 50 years ago, paramutation describes a trans acting allelic interaction that results in a heritable change in gene expression.…”
mentioning
confidence: 99%
“…Used in the manufacture of polycarbonate plastics and epoxy resins, exposure can occur via plastic food containers (especially when heated or microwaved), food and drink cans, baby bottles, and carbonless paper (reviewed in [191,192]). As a result, 95% of adults who were tested have detectable levels of BPA in their urine [193].…”
Section: Bisphenol a (Bpa)mentioning
confidence: 99%
“…Rats that were exposed to oral DEHP (313 and 573 mg/kg/day) between E0-20 had reduced number of pups in their litters as well as decreased mean pups weights. Similarly mice that were exposed to DEHP (0, 44,91,191, and 293 mg/kg/day) between E0-17 showed a dose-dependent increase in number of embryonic resorptions as well as other major malformations, including cardiovascular malformation and skeletal defects with the two highest doses [231]. More recently, a shorter exposure to DEHP (0, 250, 500, and 1000 mg/kg/day) during first 4 to 6 days of pregnancy, in mice, showed that the highest dose leads to extensive embryonic resorption at the end of exposure period, due to reduced endometrial receptivity (characterized by insufficient decidualization), which is associated with an increase in ESR1, PR, and E-cadherin and inhibition of MAPK and Nf-κB signaling pathways [232].…”
Section: Dehp and In Vivo Studiesmentioning
confidence: 99%
“…A review article examining all environmental endocrinedisrupting chemicals (EDCs) affecting fertility disorders in females identified similar toxins including methoxychlor (MTX, pesticide), genistein (phytoestrogen), and bisphenol A (BPA, plasticizer) [59]. While the EDCs directly affected the fertility of the female mouse exposed, they also affected future generations and caused differential methylation patterns suggesting epigenetic effects.…”
Section: Epigenetic Causes Of Dormentioning
confidence: 99%